B-mode ultrasonography and gray scale histogram for evaluation of the nuchal ligament in Quarter horse - Santos, Wildemberto A. [UNESP]; Vettorato, Michel C. [UNESP]; Fogaça, Jéssica L. [UNESP]; Mazzante, Nayara M.G. [UNESP]; Oliveira, Fernanda G. [UNESP]; Nogueira, Guilherme P. [UNESP]; Luvizotto, Maria C.R. [UNESP]; Machado, Vânia M.V. [UNESP] (FapUNIFESP (SciELO), 2019)
The gray scale histogram (GSH) makes it possible to measure the amount and distribution of gray shade frequencies, providing quantitative information on both echogenicity and echotexture of tissues. There is a need to diminish the subjectivity of the ultrasound images of the nuchal ligament (NL). This work proposes to evaluate the NL by ultrasound B-mode GSH images in different ages of Quarter horses. It used 15 healthy Quarter horses, which were classified by age into three different groups: “baby” (1), “sobreano” (2) and “adult” (3). The animals were submitted to chemical restraint for the ultrasound examination. Subsequently, the GSH tool was used in each image for statistical analysis. There was a significant difference between Mean and Mode between groups. Group 1 differed significantly when compared to Group 2 and 3. Group 2 presented superior echogenicity to Group 1 and 3. The height of the NL did not vary considerably between groups. GSH indicated that the echogenicity of NL in Quarter horses varies with age.
Keywords: B-mode; Equine; Gray scale histogram; Histogram; Morphology; Nuchal ligament; Quarter Horse; Ultrasonography